Therapy‐related myeloid neoplasms resembling juvenile myelomonocytic leukemia: a case series and review of the literature. Issue 5 (22nd December 2021) - Wintering, Astrid; Smith, Stephen; Fuh, Beng; Rangaswami, Arun; Dahl, Gary; Chien, May; Gruber, Tanja A.; Dang, Jinjun; Li, Loretta S.; Lenzen, Alicia; Savelli, Stephanie; Dvorak, Christopher C.; et al.
Abstract: Therapy‐related myeloid neoplasms (t‐MN) are a distinct subgroup of myeloid malignancies with a poor prognosis that include cases of therapy‐related myelodysplastic syndrome (t‐MDS), therapy‐related myeloproliferative neoplasms (t‐MPN) and therapy‐related acute myeloid leukemia (t‐AML). Here, we report a series of patients with clinical features consistent with juvenile myelomonocytic leukemia (JMML), an overlap syndrome of MDS and myeloproliferative neoplasms that developed after treatment for another malignancy.